EMPATHY, HUMANITY AND THE “ARMENIAN QUESTION” IN THE INTERNATIONALIST LEGAL IMAGINATION - Toufayan, Mark (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2011)
While the historiography of the “Armenian Question” has been largely subsumed in scholarly treatments of the “Eastern question”, dynamics between Turkey, the Great Powers and le droit public de l’Europe, and the failure of the League of Nations to safeguard an Armenian national home, narratives of Armenian suffering have been seen neither as integral to the history of Europe, the history of imperialism or even the history of humanitarianism. The chief aim of this article is to unearth instead how a range of interwar legal and diplomatic texts have discursively reproduced the imperial contexts within which Armenian suffering and Armenophile empathy have been framed and deployed in constituting the contradictory logics of solidarity and exclusion inherent in what some scholars have recently called, following Michel Foucault’s work on governmentality, “humanitarian government”. Through two case studies on nineteenth century “humanitarian interventionist narratives” and debates on Armenian nation- and state-building in the League, it is argued that around an imagined “Armenia” was deployed a discourse of humanitarianism through which techniques of governmental power invested and gave legal meaning to suffering and dead Armenian bodies and took charge of their “precarious lives”. Far from displacing distinctions based on race, civilization, nationalism and religion in favour of a moral paradigm of humaneness, however, a sentimentalist discourse of “humanity” permeating the international legal imagination has firmly rested on them, making it possible to group together solidarity with fellow human beings and “an inequality of lives and hierarchies of humanity”, which constitute “an aporia of humanitarian governmentality.”